2018
DOI: 10.3390/ma12010050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hatch Spacing on Melt Pool and As-built Quality During Selective Laser Melting of Stainless Steel: Modeling and Experimental Approaches

Abstract: In this study, a combined simulation and experimental approach is utilized to investigate the influence of hatch spacing on the microstructure and as-built quality of 316L stainless steel (SS) samples fabricated by selective laser melting (SLM). A three-dimensional finite element model (FEM) is employed to investigate heat transfer and melt pool during the SLM of 316L SS. The phase transformation and variation of the thermo-physical properties of the materials are considered in this model. The effects of hatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(61 citation statements)
references
References 41 publications
4
56
1
Order By: Relevance
“…It is also observed that increase in hatch spacing gives rise to higher porosity, which is also detected by Dong et al. 29…”
Section: Resultssupporting
confidence: 75%
“…It is also observed that increase in hatch spacing gives rise to higher porosity, which is also detected by Dong et al. 29…”
Section: Resultssupporting
confidence: 75%
“…Higher laser power and lower hatching distance used in the manufacturing process of Sample 2 increased the heat accumulation [41] and, as a result, the amount of sintered powder at the border of the samples. Moreover, in the crosshatch scanning strategy, which is used for Sample 2, the laser passes two times in each layer, in two directions perpendicular to each other, which also increases the total heat input and leads to the formation of large fractions of sintered powders at the sample edges.…”
Section: Resultsmentioning
confidence: 99%
“…So far, no previous research has specifically determined what area of overlap is the most appropriate for building parts. This is a complex issue, because the overlap area is associated with many factors such as hatch spacing, laser energy density, fluidity of the melting pool, and the formation of oxide film during the printing process [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%